ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN PENUMPANG PADA LAYANAN DI KM CIREMAI - Ni Nengah Rima Darmawati; Faisal Saransi; Abdul Wahid (STKIP Subang, 2026)
With the KM Ciremai, PT PELNI is one of Indonesia's main service providers for sea transportation, which is crucial for the country's people movement due to its archipelagic nature. Dissatisfaction with the service quality is shown by passenger complaints about cleanliness, timeliness, and comfort. In order to determine which aspects of service have the most impact on how customers see the KM Ciremai, this research will examine how service quality affects customer satisfaction. The researchers in this study used a descriptive correlational methodology with a quantitative approach. In order to gather primary data, 375 passengers on the KM Ciremai route between Jakarta and Jayapura were given a five-point Likert-scale questionnaire. Data gathering methods included a questionnaire as well as non-participatory observation to document crew conduct and the state of on-board amenities. There is a very substantial association (r=0.890) between service quality and passenger happiness, according to the study's results. The study found that the three most important characteristics affecting passenger evaluations were responsiveness, cleanliness, and dependability. The study's findings back up the idea that crew service quality consistency is the main factor determining customer happiness. Hence, for long-term success, management should focus on quality improvement to keep passengers loyal and trusting.